Is there an increased risk of second primary malignancy after diagnosis of thyroid cancer?. Issue 2 (15th September 2014) - Mathur, Aarti; Schneider, Eric B.; Zeiger, Martha A.
Abstract : Recent reports on the risk of developing second primary malignancies have raised concern about whether enhanced surveillance is warranted in patients with thyroid cancer. An excellent review of the incidences and types of second primary malignancies in a Korean population treated for thyroid cancer is provided in this issue of Cancer .